Alkoxycarbonylphenyl 4-alkoxycinnamate liquid crystals with antiparallel packing. Issue 13 (21st October 2021) - Tabassum, Jamila; Aziz, Aftab; Muhammad, Khushi; Tahir, Muhammad Nawaz; Vieira, André A.; Bechtold, Ivan H.; Hameed, Shahid
ABSTRACT: A series of cinnamates with two flexible chains, one as alkoxy and the other as alkoxycarbonyl, has been synthesised to investigate mesomorphic behaviour. Single crystal X-ray measurements demonstrated the crystalline structure and a dimer packing was predicted due to H-bonding interactions. Most of the compounds show SmA phase only on cooling. Only the member with shortest chains exhibited nematic along with SmA phase. A monotropic SmC phase was observed for compounds with octyloxy group. However, X-ray diffraction studies demonstrated that the SmA to SmC phase transition is not accompanied by a significant interlayer spacing reduction, which was associated to strong intermolecular interactions within the layers. In all the compounds, the mesophase supercools prior to crystallisation. GRAPHICAL ABSTRACT: uf0001